The eclipse of basic structure doctrine: an assessment of clash between three titans and Maria Chin Abdullah V Ketua Pengarah Imigresen & Anor [2021] 1 MLJ 750 - Ali Mohamed, Ashgar Ali; Ramalingam, Chithra Latha; Ahmad, Muhamad Hassan (Lexis Nexis Malaysia Sdn Bhd, 2021)
In relation to this issue it would be worthwhile to review the majority and minority’s opinion in Maria Chin case in relation to this doctrine and also to revisit the horizontal application of the stare decisis doctrine with a view of addressing the Federal Court’s flip-flop in relation to this doctrine.